Watering Down the Clean Water Act: A Critique of the NPDES Water Transfers Rule - David Eng (Washington University Journal of Law & Policy, 2011)
The Article focuses on the U.S. National Pollutant Discharge Elimination System (NPDES) permit program and its water transfers rule. Information is provided on the U.S. court case Friends of the Everglades v. South Florida Water Management District, which dealt with the regulation of contaminated water being siphoned into a drinking water supply.
Keywords: Water transfer – Law & amp; legislation; Water pollution; Agricultural laws & amp; legislation; Water supply – Florida – Everglades; Water quality management; Clean Water Act